Atomistic deformation behavior of single and twin crystalline Cu nanopillars with preexisting dislocations. (15th September 2020) - Ko, Won-Seok; Stukowski, Alexander; Hadian, Raheleh; Nematollahi, Ali; Jeon, Jong Bae; Choi, Won Seok; Dehm, Gerhard; Neugebauer, Jörg; Kirchlechner, Christoph; Grabowski, Blazej
Abstract: Molecular dynamics simulations are performed to investigate the impact of a coherent Σ3 (111) twin boundary on the plastic deformation behavior of Cu nanopillars. Our work reveals that the mechanical response of pillars with and without the twin boundary is decisively driven by the characteristics of initial dislocation sources. In the condition of comparably large pillar size and abundant initial mobile dislocations, overall yield and flow stresses are controlled by the longest, available mobile dislocation. An inverse correlation of the yield and flow stresses with the length of the longest dislocation is established and compared to experimental data. The experimentally reported subtle differences in yield and flow stresses between pillars with and without the twin boundary are likely related to the maximum lengths of the mobile dislocations. In the condition of comparably small pillar size, for which a reduction of mobile dislocations during heat treatment and mechanical loading occurs, the mechanical response of pillars with and without the twin boundary can be clearly distinguished. Dislocation starvation during deformation is more pronounced in pillars without the twin boundary than in pillars with the twin boundary because the twin boundary acts as a pinning surface for the dislocation network. Graphical abstract: Image, graphical abstract